The Implementation Of U.S Foreign Policy Towards Gaza Strip - Aulia Marcella, Rina (Aptisi Transactions On Technopreneurship (ATT), 2022)
This paper examines how the United States' foreign policy towards the Gaza conflict is being implemented. Furthermore, this paper discusses the United States' performance, attempts, technology use and outcomes in striking an agreement between Israel and Palestine. The goal of this analysis is to look at the United States' attempts in the long and near term to reintegrate the Palestinian authority into the democratic system and stabilize Gaza. According to the findings of this research, the United States has a strong commitment to community development and protection for a secure, free, democratic, and stable Palestinian government using technology in era 4.0. In order to achieve peace, the United States remains committed to a solution in which both Israel and Palestine, specifically Israel and Palestine, are equally entitled to the same level of freedom, security, and prosperity. The United States contributes to the delivery of bilateral assistance both in the economic and military fields.